The Effect of Sleep Disruption on Cardiometabolic Health - SeokHyun Hong; Da-Been Lee; Dae-Wui Yoon; Seung-Lim Yoo; Jinkwan Kim (Life)
Sleep disruption has emerged as a significant public health concern with profound implications for metabolic health. This review synthesizes current evidence demonstrating the intricate relationships between sleep disturbances and cardiometabolic dysfunction. Epidemiological studies have consistently demonstrated that insufficient sleep duration (<7 h) and poor sleep quality are associated with increased risks of obesity, type 2 diabetes, and cardiovascular disease. The underlying mechanisms are multifaceted, involving the disruption of circadian clock genes, alterations in glucose and lipid metabolism, the activation of inflammatory pathways, and the modulation of the gut microbiome. Sleep loss affects key metabolic regulators, including AMPK signaling and disrupts the secretion of metabolic hormones such as leptin and ghrelin. The latest evidence points to the role of sleep-induced changes in the composition and function of gut microbiota, which may contribute to metabolic dysfunction through modifications in the intestinal barrier and inflammatory responses. The NLRP3 inflammasome and NF-κB signaling pathways have been identified as crucial mediators linking sleep disruption to metabolic inflammation. An understanding of these mechanisms has significant implications for public health and clinical practice, suggesting that improving sleep quality could be an effective strategy for preventing and treating cardiometabolic disorders in modern society.